Covalent organic polymer, negative electrode active material, battery and electric device
By using covalent organic polymers as the negative electrode material for aqueous metal-ion batteries, the problems of poor anode stability and severe side reactions have been solved, achieving high stability and long lifespan battery performance, especially with excellent performance in a neutral electrolyte environment.
Patent Information
- Application Number
- CN202510917529.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-11-11
AI Technical Summary
Aqueous metal-ion batteries exhibit poor anode stability, severe side reactions, short cycle life, and significant capacity decay in electrolytes, especially with rapid performance degradation under acidic and alkaline electrolyte environments.
Covalent organic polymers were used as anode materials. Covalent organic polymers with specific repeating structural units were synthesized through Schiff base reaction and used as anodes in aqueous metal-ion batteries to optimize the stability and cycle performance of anode materials in neutral electrolytes.
It significantly improves the stability of the anode and the energy storage performance of the battery, extends the service life of aqueous metal-ion batteries, suppresses side reactions in a neutral electrolyte environment, and improves cycle life and capacity retention.
Smart Images

Figure CN120923706A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of ion battery technology, and in particular to a covalent organic polymer, a negative electrode active material, a battery, and an electrical device. Background Technology
[0002] The increasing energy consumption and environmental problems in recent years are driving the development of new energy storage technologies. Among them, aqueous metal-ion batteries have attracted widespread attention due to their high safety, low cost, and environmental friendliness, becoming a potential alternative technology to lithium-ion batteries. However, in practical applications, aqueous metal-ion batteries suffer from prominent problems such as poor anode stability in electrolytes, severe side reactions, short cycle life, and capacity decay, making it difficult to achieve the technical level of lithium-ion batteries. For example, traditional lead-acid batteries using lead anodes and multivalent metal anodes suffer from short cycle life and severe capacity decay, making it difficult to meet the energy storage application requirements of aqueous metal-ion batteries. Especially in acidic and alkaline electrolyte environments, anode materials are prone to adverse side reactions (such as hydrogen evolution and oxygen evolution reactions), leading to rapid performance degradation. How to effectively suppress side reactions and improve cycle life and capacity retention remains a key technical challenge that urgently needs to be solved. Therefore, developing novel anode materials with excellent electrochemical stability and cycle performance in neutral electrolytes is of great significance for improving the overall performance of aqueous metal-ion batteries and promoting their widespread application in practical energy storage. Summary of the Invention
[0003] Therefore, it is necessary to provide a covalent organic polymer suitable for neutral electrolyte environments as the negative electrode material of aqueous metal-ion batteries, so as to achieve high stability of the anode material at low potential, thereby enabling aqueous metal-ion batteries and electrical devices to have excellent cycle life and capacity retention.
[0004] In a first aspect, this application provides a covalent organic polymer having repeating structural units as shown below;
[0005]
[0006] (I)
[0007]
[0008] (II)
[0009]
[0010] (III) or
[0011]
[0012] (IV).
[0013] Secondly, this application provides a method for preparing a covalent organic polymer, comprising the following steps:
[0014] Hexacyclohexane octahydrate and an amine compound are mixed in a solvent, concentrated sulfuric acid is added, and the reaction is carried out at 160℃-195℃ to prepare the covalent organic polymer provided in the first aspect.
[0015] The amine compound is selected from dibenzo[b,e][1,4]dioxin-2,3,7,8-tetramine, 2,3,7,8-phenazinetetramine, 4a,10a-dihydrothiazanthracene-2,3,7,8-tetramine, 2,3,7,8-tetraaminophenazine-1,4,6,9-tetraone or its salts.
[0016] In some embodiments, the preparation method further satisfies at least one of the following (1) to (3):
[0017] (1) The molar ratio of the hexacyclohexane octahydrate to the amine compound is 2:(3-3.5);
[0018] (2) The organic solvent includes one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide, and acetic acid;
[0019] (3) The salt includes one or more of hydrochloride, sulfate and sulfonate.
[0020] Thirdly, this application provides a negative electrode active material, the negative electrode active material comprising the covalent organic polymer provided in the first aspect.
[0021] Fourthly, this application provides a negative electrode active layer, which includes the negative electrode active material, conductive agent, and binder provided in the first aspect.
[0022] In some embodiments, the negative electrode active material also satisfies at least one of the following characteristics (1) to (3):
[0023] (1) The conductive agent includes one or more of conductive carbon black, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0024] (2) The adhesive includes one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan;
[0025] (3) The mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode active layer is (2-8):(1-3):1.
[0026] Fifthly, this application provides a negative electrode sheet, including a current collector and the negative electrode active layer provided in the fourth aspect disposed on the current collector.
[0027] In a sixth aspect, this application provides a battery comprising the negative electrode, positive electrode, and electrolyte provided in the fifth aspect.
[0028] In some embodiments, the battery further satisfies at least one of the features shown in (1) to (3) below:
[0029] (1) The electrolyte contains divalent metal ions;
[0030] Optionally, the divalent metal ion includes Mg. 2+ and / or Ca 2+ .
[0031] (2) The electrolyte is a neutral electrolyte solution;
[0032] Optionally, the pH of the neutral electrolyte is 7 ± 0.2;
[0033] (3) The positive electrode active material used in the positive electrode sheet includes Prussian blue compounds;
[0034] Optionally, the Prussian blue compound structure includes a transition metal;
[0035] Further optionally, the transition metal includes one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce.
[0036] In a seventh aspect, this application provides an electrical device comprising the battery provided in the sixth aspect.
[0037] Compared with traditional technologies, the beneficial effects of the technical solution in this application include:
[0038] The covalent organic polymer with repeating structural units provided in this application, when used as a negative electrode material, can significantly reduce the anode potential, improve the stability of the anode, and significantly improve the electrical performance of the battery, especially the anode of aqueous metal-ion batteries, thereby improving the energy storage performance, cycle life, and capacity retention of aqueous metal-ion batteries. The covalent organic polymer provided in this application, by controlling the molecular structure of the material, can be applied in aqueous metal-ion batteries as a negative electrode material, greatly optimizing the insertion / extraction process of aqueous metal ions, reducing the kinetic impedance of the reaction, and extending the service life of aqueous metal-ion batteries. Simultaneously, the covalent organic polymer provided in this application, as a negative electrode material, is also suitable for operation in neutral electrolytes, and can greatly suppress side reactions occurring at the anode under neutral electrolyte conditions, overcoming the technical difficulties commonly encountered by the anodes of traditional aqueous metal-ion batteries in weakly acidic or alkaline electrolytes, such as hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and material corrosion. Attached Figure Description
[0039] Figure 1 Infrared spectrum of the covalent organic polymer COPs-1 prepared in this application.
[0040] Figure 2 Solid-state nuclear magnetic resonance of the covalent organic polymer COPs-1 prepared for this application 13 C-spectrum.
[0041] Figure 3 Infrared spectrum of the covalent organic polymer COPs-2 prepared in this application.
[0042] Figure 4 Solid-state nuclear magnetic resonance of the covalent organic polymer COPs-2 prepared for this application 13 C-spectrum.
[0043] Figure 5 The long-cycle performance of the aqueous Mg-ion full cell 1 and the aqueous Ca-ion full cell 1 prepared in this application. Detailed Implementation
[0044] To facilitate understanding of this application, a more complete description will be provided below with reference to the accompanying drawings. Preferred embodiments of this application are shown in the drawings. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of this application.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0046] As used herein, "optional," "optional," and "optional" refer to either "with" or "without" parallel options. If multiple "optional" entries appear in a technical solution, each "optional" entry is independent unless otherwise specified and there are no contradictions or mutual constraints. The term "and / or" as used herein includes any and all combinations of one or more related listed items. Unless otherwise specified, "multiple," "multiple," etc., as used herein refer to a quantity greater than 2 or equal to 2; for example, "one or more" indicates one, two, or more than two. In open-ended technical features or solutions described herein using words such as "containing," "including," and "comprising," unless otherwise specified, additional members beyond the listed members are not excluded. This can be considered as providing both a closed-ended feature or solution consisting of the listed members and an open-ended feature or solution that includes additional members beyond the listed members.
[0047] In this application, the terms "first aspect," "second aspect," "third aspect," "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0048] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0049] The term "heterocyclic group" refers to a cycloalkyl group in which at least one carbon atom is replaced by a non-carbon atom, which can be an N atom, O atom, S atom, etc., and can be a saturated ring or a partially unsaturated ring. Phrases containing this term, such as "C4-C9 heterocyclic group," refer to heterocyclic groups containing 4-9 carbon atoms, and each occurrence can independently be a C4 heteroalkyl, C5 heteroalkyl, C6 heteroalkyl, C7 heteroalkyl, C8 heteroalkyl, or C9 heteroalkyl. Suitable examples include, but are not limited to: dihydropyridyl, tetrahydropyridyl (piperidinyl), tetrahydrothiophenyl, sulfur-oxidized tetrahydrothiophenyl, tetrahydrofuranyl, tetrahydroquinolinyl, tetrahydroisoquinolinyl, and dihydroindolyl.
[0050] The term "cycloalkyl" refers to a non-aromatic hydrocarbon containing a ring of carbon atoms, which can be monocycloalkyl, spirocycloalkyl, or bridged cycloalkyl. Phrases containing this term, such as "C3-C9 cycloalkyl," refer to cycloalkyl groups containing 3-9 carbon atoms, and each occurrence can independently be C3, C4, C5, or C6 cycloalkyl. Suitable examples include, but are not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cycloheptyl. Additionally, "cycloalkyl" may contain one or more double bonds; representative examples of cycloalkyl groups containing double bonds include cyclopentenyl, cyclohexenyl, cyclohexadienyl, and cyclobutadienyl.
[0051] The term "aryl" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing one hydrogen atom. It can be a monocyclic aryl, a fused-ring aryl, or a polycyclic aryl; for polycyclic compounds, at least one ring must be an aromatic ring system. For example, "C5~C..." 20 "Aryl" refers to an aryl group containing 5 to 20 carbon atoms. Each time it appears, it can independently be C5 aryl, C6 aryl, C7 aryl, C8 aryl, C9 ... 10 Aryl, C 14 Aryl, C 18 Aryl or C 20 Aryl group. Suitable examples include, but are not limited to: benzene, biphenyl, naphthalene, anthracene, phenanthrene, dinaphthalene, triphenylene and their derivatives. Understandably, multiple aryl groups may also be interrupted by short non-aromatic units (e.g., <10% non-H atoms, such as C, N or O atoms), specifically acenaphthene, fluorene, or 9,9-diarylfluorene, triarylamines, and diaryl ether systems should also be included in the definition of aryl.
[0052] In view of the technical problems of the anode in aqueous metal-ion batteries in practical applications, such as poor stability of the anode in the electrolyte, serious side reactions, short cycle life and significant capacity decay, this application aims to provide a novel covalent organic polymer (COPs) material as a negative electrode material to solve the technical problems of the anode in aqueous metal-ion batteries.
[0053] In a first aspect, this application provides a covalent organic polymer having repeating structural units as shown below;
[0054]
[0055] (I)
[0056]
[0057] (II)
[0058]
[0059] (III) or
[0060]
[0061] (IV).
[0062] The covalent organic polymer provided in this application introduces electron-donating bonds into the conjugated ring, which improves the electron cloud density distribution and ion diffusion capability of the covalent organic polymer. As a negative electrode material, it can significantly reduce the anode potential, improve the stability of the anode, and significantly improve the battery, especially the energy storage performance, cycle life and capacity retention of aqueous metal-ion batteries.
[0063] Furthermore, the covalent organic polymer provided in this application, by regulating the molecular structure of the material, is particularly suitable as a negative electrode material for aqueous divalent metal ion batteries (ABIBs), optimizes the insertion / extraction process of aqueous divalent metal ions, reduces the kinetic impedance of the reaction, and extends the service life of aqueous divalent metal ion batteries.
[0064] Furthermore, the covalent organic polymer provided in this application, as a negative electrode material, is also suitable for operation in neutral electrolytes. It can greatly suppress the side reactions that occur at the anode under neutral electrolyte conditions, overcome the problems of HER reaction, OER reaction and material corrosion that are common in weak acid or alkaline electrolytes, and achieve low potential, high cycle stability and excellent electrochemical performance.
[0065] The covalent organic polymer provided in this application, as a negative electrode active material, enables the anode to have low potential, excellent cycle stability and good electrochemical performance, providing technical support for the practical application of aqueous metal-ion batteries, especially aqueous divalent metal-ion batteries, and has important promotional value.
[0066] Secondly, this application provides a method for preparing a covalent organic polymer, comprising the following steps:
[0067] Hexacyclohexane octahydrate and an amine compound are mixed in a solvent, and concentrated sulfuric acid (98 wt%) is added. The mixture is then reacted at 160°C-195°C to prepare the covalent organic polymer provided in the first aspect.
[0068] In some embodiments, the amine compound is selected from dibenzo[b,e][1,4]dioxin-2,3,7,8-tetramine (TADD), 2,3,7,8-phenazinetetramine (TAPZ), 4a,10a-dihydrothiazanthracene-2,3,7,8-tetramine (TADT), 2,3,7,8-tetraaminophenazine-1,4,6,9-tetraone (TAPT), or a salt thereof.
[0069] The specific structural formulas of the amine compounds are as follows:
[0070]
[0071] Dibenzo[b,e][1,4]dioxin-2,3,7,8-tetraamine (TADD)
[0072]
[0073] 2,3,7,8-Phenazinetetramine (TAPZ)
[0074]
[0075] 4a,10a-Dihydrothiaphene-2,3,7,8-Tetraamine (TADT)
[0076]
[0077] 2,3,7,8-Tetraaminophenazine-1,4,6,9-tetraone (TAPT)
[0078] In some embodiments, the salt includes one or more of hydrochloride, sulfate, and sulfonate.
[0079] As a non-limiting example, the amine compound is selected from one or more of dibenzo[b,e][1,4]dioxin-2,3,7,8-tetramine (TADD), dibenzo[b,e][1,4]dioxin-2,3,7,8-tetramine salt, 2,3,7,8-phenazine tetramine (TAPZ), 2,3,7,8-phenazine tetramine salt, 4a,10a-dihydrothiazanthracene-2,3,7,8-tetramine (TADT), 4a,10a-dihydrothiazanthracene-2,3,7,8-tetramine salt, 2,3,7,8-tetraaminophenazine-1,4,6,9-tetraone (TAPT), and 2,3,7,8-tetraaminophenazine-1,4,6,9-tetraone salt.
[0080] This application synthesizes a series of novel covalent organic polymers (COPs) using hexacyclohexane octahydrate and amine compounds as raw materials via Schiff base reaction. These COPs can significantly improve anode stability, as well as significantly improve the energy storage performance, cycle life, and capacity retention of aqueous metal-ion batteries.
[0081] In some embodiments, this application synthesizes a series of novel covalent organic polymers (COPs) and further realizes their use as negative electrode materials in a neutral electrolyte environment, enabling efficient and reversible storage of aqueous metal-ion batteries, especially aqueous divalent metal-ion batteries.
[0082] In some embodiments, the reaction temperature in the preparation process of the covalent organic polymer includes, but is not limited to, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, or any combination thereof and values within such ranges.
[0083] In some embodiments, the molar ratio of the hexacyclohexane octahydrate to the amine compound is 2:(3-3.5).
[0084] In some embodiments, the solvent includes one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide, and acetic acid.
[0085] Thirdly, this application provides a negative electrode active material, the negative electrode material comprising the covalent organic polymer provided in the first aspect, or a covalent organic polymer prepared by the preparation method of the covalent organic polymer provided in the second aspect.
[0086] Fourthly, this application provides a negative electrode active layer, which includes the negative electrode active material, conductive agent, and binder provided in the first aspect.
[0087] In some embodiments, the conductive agent includes one or more of conductive carbon black, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0088] In some embodiments, the adhesive includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0089] In some embodiments, the mass ratio of the covalent organic polymer, the conductive agent, and the binder is (2-8):(1-3):1. As non-limiting examples, this includes, but is not limited to, 2:1:1, 2:2:1, 2:3:1, 3:1:1, 3:3:1, 5:1:1, 5:3:1, 6:3:1, 7:2:1, 8:1:1, 8:3:1, or any range formed by both of the foregoing and values within that range.
[0090] Fifthly, this application provides a negative electrode sheet, including a current collector and the negative electrode active layer provided in the fourth aspect disposed on the current collector.
[0091] In some embodiments, the method for preparing the negative electrode sheet includes the following steps:
[0092] The negative electrode active material is dispersed in a solvent to form a negative electrode slurry.
[0093] The negative electrode active layer is formed by coating the negative electrode slurry onto at least one side of the negative electrode current collector, and then the negative electrode sheet is obtained after drying, cold pressing and other processes.
[0094] In some embodiments, the solvent may be selected from, but is not limited to, any of the solvents described in the foregoing embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode current collector coated with the negative electrode slurry may be a single surface of the negative electrode current collector or both surfaces of the negative electrode current collector.
[0095] In a sixth aspect, this application provides a battery comprising the negative electrode, positive electrode, and electrolyte provided in the fifth aspect.
[0096] In some embodiments, the electrolyte contains divalent metal ions. As a non-limiting example, the divalent metal ions include Mg. 2+ and / or Ca 2+ .
[0097] In some embodiments, the electrolyte is a neutral electrolyte. As a non-limiting example, the pH of the neutral electrolyte is 7 ± 0.2.
[0098] In some embodiments, the pH of the neutral electrolyte is 6.8-7.2. As a non-limiting example, the pH includes, but is not limited to, 6.8, 6.9, 7, 7.1, 7.2, or any combination thereof and values within that range.
[0099] In some embodiments, the positive electrode active material used in the positive electrode sheet includes Prussian blue compounds.
[0100] In some embodiments, the Prussian blue compound structure includes a transition metal element.
[0101] In some embodiments, the transition metal element includes one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. As a non-limiting example, the Prussian blue compound is selected from one or more of Prussian blue copper-iron, Prussian blue manganese, and Prussian blue cobalt.
[0102] In some embodiments, the positive electrode includes a current collector and a positive active layer disposed on the current collector.
[0103] In some embodiments, the positive electrode active layer includes the positive electrode active material, a conductive agent, and a binder.
[0104] As a non-limiting example, the conductive agent includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0105] As a non-limiting example, the adhesive includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.
[0106] In some embodiments, the mass ratio of the Prussian blue compound, the conductive agent, and the binder is (2-8):(1-3):1. As non-limiting examples, this includes, but is not limited to, ranges of 2:1:1, 2:2:1, 2:3:1, 3:1:1, 3:3:1, 5:1:1, 5:3:1, 6:3:1, 7:2:1, 8:1:1, 8:3:1, or any combination thereof, and values within those ranges.
[0107] In some embodiments, the method for preparing the positive electrode sheet includes the following steps:
[0108] The positive electrode active material, the conductive agent, and the binder are dispersed in a solvent to form a positive electrode slurry.
[0109] The positive electrode active layer is formed by coating the positive electrode slurry onto at least one side of the positive electrode current collector. After drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0110] In some embodiments, the solvent may be selected from, but is not limited to, any of the solvents described in the foregoing embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode current collector coated with the positive electrode slurry may be a single surface of the positive electrode current collector or both surfaces of the positive electrode current collector.
[0111] In a sixth aspect, this application provides an electrical device comprising the battery provided in the fifth aspect.
[0112] It should be noted that experimental methods in the following embodiments of this application, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All commonly used chemical reagents used in the embodiments are commercially available products, or can be prepared by those skilled in the art using known methods.
[0113] The hexacyclohexane octahydrate (Hex-8H2O) involved in the embodiments of this application is CAS 527-31-1.
[0114] Example 1
[0115] The covalent organic polymer and its preparation method provided in this embodiment are as follows:
[0116] Under an inert atmosphere, hexacyclohexane octahydrate (Hex-8H2O) and dibenzo[b,e][1,4]dioxin-2,3,7,8-tetraaminetetrahydrochloride (TADD-4HCl, CAS: 34294-67-2) were added to a round-bottom flask containing 20 mL of N-methyl-2-pyrrolidone (NMP) in a molar ratio of 2:3 and mixed thoroughly. Then, 2 mL of concentrated sulfuric acid (98 wt%) was added dropwise. The mixture was heated to 185 °C and reacted for 3 days. After the reaction was stopped, the mixture was filtered to separate the dark brown precipitate. The precipitate was washed successively with water, acetone, and acetonitrile, and then purified by Soxhlet extraction with methanol for 3 days. The precipitate was then dried under vacuum at 100 °C for 10 hours to obtain the covalent organic polymer, denoted as COPs-1.
[0117] Example 2
[0118] The covalent organic polymer and its preparation method provided in this embodiment are as follows:
[0119] Under an inert atmosphere, hexacyclohexane octahydrate (Hex-8H2O) and 2,3,7,8-phenazine tetraamine hydrochloride (TAPZ-4HCl, CAS: 260354-29-8) were added to a round-bottom flask containing 20 mL of N-methyl-2-pyrrolidone (NMP) in a molar ratio of 2:3 and mixed thoroughly. Then, 2 mL of concentrated sulfuric acid (98 wt%) was added dropwise. The mixture was heated to 185 °C and reacted for 3 days. After the reaction was stopped, the mixture was filtered to separate the dark brown precipitate. The precipitate was washed successively with water, acetone, and acetonitrile, and then purified by Soxhlet extraction with methanol for 3 days. The precipitate was then dried under vacuum at 100 °C for 10 hours to obtain the covalent organic polymer, denoted as COPs-2.
[0120] Example 3
[0121] The covalent organic polymer and its preparation method provided in this embodiment are as follows:
[0122] Under an inert atmosphere, hexacyclohexane octahydrate (Hex-8H2O) and 4a,10a-dihydrothiathianthracene-2,3,7,8-tetraamine (TADT) were added in a molar ratio of 2:3 to a round-bottom flask containing 20 mL of N-methyl-2-pyrrolidone (NMP). The mixture was thoroughly mixed, and then 2 mL of concentrated sulfuric acid (98 wt%) was added dropwise. The mixture was heated to 185 °C and reacted for 3 days. After the reaction was stopped, the mixture was filtered to separate the dark brown precipitate. The precipitate was washed successively with water, acetone, and acetonitrile, and then purified by Soxhlet extraction with methanol for 3 days. The precipitate was then dried under vacuum at 100 °C for 10 hours to obtain the covalent organic polymer, denoted as COPs-3.
[0123] Example 4
[0124] The covalent organic polymer and its preparation method provided in this embodiment are as follows:
[0125] Under an inert atmosphere, hexacyclohexane octahydrate (Hex-8H2O) and 2,3,7,8-tetraaminophenazin-1,4,6,9-tetraone (TAPT, CAS: 2857099-14-8) were added to a round-bottom flask containing 20 mL of N-methyl-2-pyrrolidone (NMP) in a molar ratio of 2:3 and mixed thoroughly. Then, 2 mL of concentrated sulfuric acid (98 wt%) was added dropwise. The mixture was heated to 185 °C and reacted for 3 days. After the reaction was stopped, the mixture was filtered to separate the dark brown precipitate. The precipitate was washed successively with water, acetone, and acetonitrile, and then purified by Soxhlet extraction with methanol for 3 days. The precipitate was then dried under vacuum at 100 °C for 10 hours to obtain the covalent organic polymer, denoted as COPs-4.
[0126] Example 5
[0127] This embodiment provides a type of negative electrode sheet and its preparation method, as detailed below:
[0128] Negative electrode 1 and its preparation: The covalent organic polymer COPs-1 prepared in Example 1 was mixed with a conductive agent (Ketjen Black) and a binder (PVDF) at a mass ratio of 6:3:1. The mixture was then added to 10 mL of N-methylpyrrolidone (NMP) at a material-to-liquid ratio of 5:1 and mixed evenly. The mixture was then coated onto carbon cloth and dried to obtain negative electrode 1.
[0129] Negative electrode 2 and its preparation: The covalent organic polymer COPs-2 prepared in Example 2 was mixed with a conductive agent (Ketjen Black) and a binder (PVDF) at a mass ratio of 6:3:1. The mixture was then added to 10 mL of N-methylpyrrolidone (NMP) at a material-to-liquid ratio of 5:1 and mixed evenly. The mixture was then coated onto carbon cloth and dried to obtain negative electrode 2.
[0130] Negative electrode 3 and its preparation: The covalent organic polymer COPs-3 prepared in Example 3 was mixed with a conductive agent (Ketjen Black) and a binder (PVDF) at a mass ratio of 6:3:1. The mixture was then added to 10 mL of N-methylpyrrolidone (NMP) at a material-to-liquid ratio of 5:1 and mixed evenly. The mixture was then coated onto carbon cloth and dried to obtain negative electrode 3.
[0131] Negative electrode 4 and its preparation: The covalent organic polymer COPs-4 prepared in Example 4 was mixed with a conductive agent (Ketjen Black) and a binder (PVDF) at a mass ratio of 6:3:1. The mixture was then added to 10 mL of N-methylpyrrolidone (NMP) at a material-to-liquid ratio of 5:1 and mixed evenly. The mixture was then coated onto carbon cloth and dried to obtain negative electrode 4.
[0132] Example 6
[0133] This embodiment uses a hydrothermal coprecipitation method to synthesize a Prussian copper-iron (CuFe-PBA) cathode material. The specific method is as follows:
[0134] CuSO4 solution was added dropwise to K3Fe(CN)6 solution at a molar ratio of 2:1. The mixture was then stirred vigorously at 80°C for 1 hour. After stabilization, the mixture was washed several times with deionized water and dried overnight in a vacuum oven at 80°C to obtain olive-green Prussian blue copper-iron (CuFe-PBA).
[0135] Example 7
[0136] This embodiment provides a type of positive electrode sheet and its preparation method, as detailed below:
[0137] The Prussian blue copper iron (CuFe-PBA) prepared in Example 6 was mixed with a conductive agent (Ketjen black) and a binder (PVDF) at a mass ratio of 7:2:1. The mixture was then added to 10 mL of N-methylpyrrolidone (NMP) at a material-to-liquid ratio of 5:1 and mixed evenly. The mixture was then coated onto carbon cloth and dried to obtain a positive electrode sheet.
[0138] Example 8
[0139] This embodiment provides a type of aqueous divalent metal-ion full battery and its assembly method, as detailed below:
[0140] The negative electrode 1 prepared in Example 5, the positive electrode 1 prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was either a saturated MgCl2 electrolyte or a saturated CaCl2 electrolyte. The pH of the electrolyte was adjusted to 7.0. The positive electrode and the negative electrode were spaced 1 cm apart. Aqueous Mg-ion full cell 1 and aqueous Ca-ion full cell 1 were assembled respectively.
[0141] The negative electrode 2 prepared in Example 5, the positive electrode 2 prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was either a saturated MgCl2 electrolyte or a saturated CaCl2 electrolyte. The pH of the electrolyte was adjusted to 7.0. The positive electrode and the negative electrode were spaced 1 cm apart. Aqueous Mg-ion full battery 2 and aqueous Ca-ion full battery 2 were assembled respectively.
[0142] The negative electrode 3 prepared in Example 5, the positive electrode 3 prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was either a saturated MgCl2 electrolyte or a saturated CaCl2 electrolyte. The pH of the electrolyte was adjusted to 7. The positive electrode and the negative electrode were spaced 1 cm apart. Aqueous Mg-ion full battery 3 and aqueous Ca-ion full battery 3 were assembled respectively.
[0143] The negative electrode 4 prepared in Example 5, the positive electrode 4 prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was either a saturated MgCl2 electrolyte or a saturated CaCl2 electrolyte. The pH of the electrolyte was adjusted to 7.0. The positive electrode and the negative electrode were spaced 1 cm apart. Aqueous Mg-ion full battery 4 and aqueous Ca-ion full battery 4 were assembled respectively.
[0144] The negative electrode 1 prepared in Example 5, the positive electrode 1 prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was a saturated MgCl2 electrolyte, and the pH of the electrolyte was adjusted to 2.5. The positive electrode and the negative electrode were spaced 1 cm apart, and an aqueous Mg-ion full cell 5 was obtained.
[0145] The negative electrode 1 prepared in Example 5, the positive electrode prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was a saturated MgCl2 electrolyte, and the pH of the electrolyte was adjusted to 3.5. The positive electrode and the negative electrode were spaced 1 cm apart, and an aqueous Mg-ion full cell 6 was obtained.
[0146] The negative electrode 1 prepared in Example 5, the positive electrode prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was a saturated CaCl2 electrolyte, and the pH of the electrolyte was adjusted to 4.5. The positive electrode and the negative electrode were spaced 1 cm apart, and an aqueous Ca-ion full cell 7 was obtained.
[0147] The negative electrode 1 prepared in Example 5, the positive electrode prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was a saturated CaCl2 electrolyte, and the pH of the electrolyte was adjusted to 5.5. The positive electrode and the negative electrode were spaced 1 cm apart, and an aqueous Ca-ion full cell 8 was obtained.
[0148] The negative electrode 1, positive electrode (MnO2), and electrolyte prepared in Example 5 were assembled into a battery. The electrolyte was a saturated MgCl2 electrolyte, and the pH of the electrolyte was adjusted to 7. The positive electrode and negative electrode were spaced 1 cm apart, and an aqueous Mg-ion full cell 9 was obtained.
[0149] Comparative Example 1
[0150] The negative electrode, the positive electrode prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was a saturated MgCl2 electrolyte, and the pH of the electrolyte was adjusted to 7. The positive electrode and the negative electrode were spaced 1 cm apart, and the battery 10 was obtained.
[0151] The negative electrode sheet of this comparative example was prepared by mixing the covalent organic framework material COF-1 prepared in Example 1 of Publication No. CN118373988A with a conductive agent (Ketjen Black) and a binder (PVDF) at a mass ratio of 6:3:1. The mixture was then added to 10 mL of N-methylpyrrolidone (NMP) at a material-to-liquid ratio of 5:1 and mixed evenly. The mixture was then coated on carbon cloth and dried to obtain the negative electrode sheet.
[0152] Comparative Example 2
[0153] The negative electrode, the positive electrode prepared in Example 7, and the electrolyte were assembled into a battery. The electrolyte was a saturated MgCl2 electrolyte, and the pH of the electrolyte was adjusted to 7. The positive electrode and the negative electrode were spaced 1 cm apart, and the battery 11 was obtained.
[0154] The negative electrode sheet of this comparative example is made by mixing a porous aromatic framework material with a conductive agent (Ketjen Black) and a binder (PVDF) at a mass ratio of 6:3:1, adding it to 10 mL of N-methylpyrrolidone (NMP) at a material-to-liquid ratio of 5:1 and mixing evenly. Then, it is coated on carbon cloth and dried to obtain the negative electrode sheet.
[0155] The preparation method of the porous aromatic framework material is as follows:
[0156] Under an inert atmosphere, hexacyclohexane octahydrate (Hex-8H2O) and 1,2,4,5-phenyltetramine tetrahydrochloride were added in a molar ratio of 2:3 to a round-bottom flask containing 20 mL of N-methyl-2-pyrrolidone (NMP). The mixture was thoroughly mixed, and then 2 mL of concentrated sulfuric acid was added dropwise. The mixture was heated to 185 °C and reacted for 3 days. After the reaction was stopped, the mixture was filtered to separate the dark brown precipitate. The precipitate was washed successively with water, acetone, and acetonitrile, and then purified by Soxhlet extraction with methanol for 3 days. The precipitate was then dried under vacuum at 100 °C for 10 hours to obtain a covalent organic framework (COF) material.
[0157] Application Example 1
[0158] The 13 groups of aqueous divalent metal-ion full cells prepared in Example 8, as well as the batteries prepared in Comparative Examples 1 and 2, were tested for their electrical performance using a constant current charge-discharge method on the Xinwei Battery Testing System. The test results are shown in Table 1 and Appendix. Figure 1 As shown.
[0159] Table 1: Electrical performance test results of aqueous divalent metal ion full cells
[0160]
[0161] As shown in Table 1, the covalent organic polymers (COPs) prepared in this application significantly reduce the anode potential, thereby significantly improving the ultrastability of the anode in aqueous divalent metal ion batteries. Furthermore, the results in Table 1 and the appendix... Figure 5 The results show that the prepared anode material exhibits an ultra-long cycle life (20 A g) in neutral electrolyte. -1 (60,000 cycles), suitable for magnesium ions (Mg) 2+ ) and calcium ions (Ca 2+ The aqueous divalent metal ion energy storage system provides a technological foundation for further promoting the large-scale application of aqueous metal batteries. However, the negative electrode materials prepared in batteries 10 and 11 of Comparative Examples 1-2 are difficult to achieve the effects of the embodiments of this application.
[0162] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0163] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. A covalent organic polymer, characterized in that, It has repeating structural units as shown below; (I)、 (II) (III) or (IV).
2. A method for preparing covalent organic polymers, characterized in that, Includes the following steps: Hexacyclohexane octahydrate and an amine compound are mixed in a solvent, concentrated sulfuric acid is added, and the reaction is carried out at 160℃-195℃ to prepare the covalent organic polymer of claim 1. The amine compound is selected from dibenzo[b,e][1,4]dioxin-2,3,7,8-tetramine, 2,3,7,8-phenazinetetramine, 4a,10a-dihydrothiazanthracene-2,3,7,8-tetramine, 2,3,7,8-tetraaminophenazine-1,4,6,9-tetraone or its salts.
3. The method for preparing the covalent organic polymer according to claim 2, characterized in that, The preparation method also satisfies at least one of the following (1) to (3): (1) The molar ratio of the hexacyclohexane octahydrate to the amine compound is 2:(3-3.5); (2) The solvent includes one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide, and acetic acid; (3) The salt includes one or more of hydrochloride, sulfate and sulfonate.
4. A negative electrode active material, characterized in that, The negative electrode active material includes the covalent organic polymer of claim 1.
5. A negative electrode active layer, characterized in that, The negative electrode active layer comprises the negative electrode active material as described in claim 4, a conductive agent, and a binder.
6. The negative electrode active layer according to claim 5, characterized in that, The negative electrode active layer also satisfies at least one of the following features (1) to (3): (1) The conductive agent includes one or more of conductive carbon black, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. (2) The adhesive includes one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan; (3) The mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode active layer is (2-8):(1-3):
1.
7. A negative electrode sheet, characterized in that, It includes a current collector and the negative electrode active layer of claim 5 or 6 disposed on the current collector.
8. A battery, characterized in that, It includes the negative electrode, positive electrode, and electrolyte as described in claim 7.
9. The battery according to claim 8, characterized in that, The battery also satisfies at least one of the following features (1) to (3): (1) The electrolyte contains divalent metal ions; Optionally, the divalent metal ion includes Mg. 2+ and / or Ca 2+ ; (2) The electrolyte is a neutral electrolyte solution; Optionally, the pH of the neutral electrolyte is 7 ± 0.2; (3) The positive electrode active material used in the positive electrode sheet includes Prussian blue compounds; Optionally, the structure of the Prussian blue compound includes a transition metal element; Further optionally, the transition metal element includes one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce.
10. An electrical appliance, characterized in that, The electrical device includes the battery as described in claim 8 or 9.
Citation Information
Patent Citations
Covalent organic framework material, preparation method thereof, electrode material, battery and application
CN118373988A